Green Supply Chain Management Consideration Using Analitycal Network Process (ANP) Method in Supplier Selection in PT. XYZ - Satria Fitrah Wicaksana; Bambang Syairudin (IPTEK Journal of Proceedings Series, 2019)
The concept of Green Supply Chain Management (GSCM) is to integrate supply chain management with consumers, which includes the process of resource extraction, product design and development, distribution, waste disposal and recycle processes based on the thought of saving the environment. The problem found in this study is that suppliers pay little attention to environmental aspects as well as safety, delivery delays and quality. Government regulations related to the industry regarding the environment and the increasing number of people who switch to green products compel industry players to start incorporating environmental aspects into each of their production processes. This study uses the green supply chain management (GSCM) concept that integrates environmental aspects into business processes in the industry and discusses standardization of supplier selection. Selection of suppliers is an important problem that must be consider by the company in order to get suppliers who can support and improve the competitiveness of the company. The sample in this study was top management who worked at PT XYZ. Data collection techniques is using a questionnaire. The analysis of the green supplier selection was carry out using the Analytical Network Process (ANP) method because ANP is one method that is able to represent the importance of various parties by considering the interrelationships between the criteria and the existing sub-criteria. Criteria for selecting suppliers are financial, environmental, quality, technical (service). An ANP linkage model is base on the identification of criteria and sub-criteria and the interrelationships between the two. All of the criteria and sub-criteria are compare with each other. The comparison scores are process and obtained scores for each alternative supplier. The results is obtained data quality criteria have a score of 0.319, environmental criteria have a score of 0.254, technical criteria (service) has a score of 0.216 financial criteria has a score of 0.211. The supplier's recommendation is PT C because it has the highest score of 0.363